Are Fluctuations in Energy Consumption Transitory or Permanent? Evidence From a Panel of East Asia & Pacific Countries - Kum, Hakan (International Journal of Energy Economics and Policy, 2012)
This paper examines the unit root properties of energy consumption per capita for 15 East Asia & Pacific countries employing the Lagrange Multiplier (LM) panel unit root test with one structural break for 1971-2007. When we apply the LM univariate test without break, we find a unit root in per capita consumption for Brunei Darussalam, Indonesia, Japan, North Korea, South Korea and Myanmar. However, when we apply LM unit root with structural break, we find overwhelming evidence that there is no unit root in per capita energy consumption for these 15 East Asia & Pacific countries. Keywords: Energy consumption; Unit root; Stationarity; Lagrange Multiplier; Panel unit root test. JEL Classifications: C23; Q43